Efeitos do estresse neonatal por lipopolissacarídeo sobre a resposta a um estímulo inflamatório em camundongos - Barth, Cristiane Raquel (2015)
Neonatal exposure to lipopolysaccharides (LPS) generates a stressful stimulus capable of affecting the development of important systems, which causes lasting behavioral and neuroendocrine alterations. The aim of this study is to evaluate the response to an inflammatory stimulus in Balb/c mice exposed to LPS-induced neonatal stress at different ages and genders. Mice underwent intraperitonial injections on postnatal days 3 and 10 with either LPS (100ug/Kg) or saline solution. After 21 or 60 days of age, either saline solution was injected or an inflammatory stimulus was induced by the injection of 1% carrageenan. Inflammatory cytokines, reactive oxygen species and NETs production were measured in the peritoneal lavage. Our findings indicate that LPS-induced neonatal stress can reduce inflammatory cytokines in young animals, males and females. In adults, however, only females showed the same response pattern. In nLPS group, an increase in NETs production was observed in animals that were 60-days-old when compared to 21-days-old in both genders, which indicates an effect of neonatal stress on the ontogeny of NETs formation. The production of ROS was not affected by neonatal stress, even though an increased production was found among adults regardless of neonatal intervention. The results shown here indicate that LPS-induced neonatal stress can alter cytokine production in response to inflammatory stimuli at different ages, in a gender dependent way. Moreover, it seems like the formation of NETs throughout life is also influenced by alterations undergone during the neonatal period.